A population pharmacokinetic meta‐analysis of custirsen, an antisense oligonucleotide, in oncology patients and healthy subjects. (2nd May 2017) - Edwards, Alena Y.; Elgart, Anna; Farrell, Colm; Barnett‐Griness, Ofra; Rabinovich‐Guilatt, Laura; Spiegelstein, Ofer
Abstract : Aims: Custirsen (OGX‐011/TV‐1011), a second‐generation antisense oligonucleotide that reduces clusterin production, is under investigation with chemotherapy in prostate and lung cancer. This meta‐analysis evaluated the population pharmacokinetics (PK) of custirsen in cancer patients and healthy subjects. Methods: The population PK analysis used custirsen plasma concentrations from five Phase 1 studies, one Phase 1/2 study, and one Phase 3 study in two stages. Cancer patients received multiple doses of custirsen (40–640 mg intravenously over 120 min) with chemotherapy; healthy subjects received single or multiple doses (320–640 mg). An interim population PK model was developed using a nonlinear mixed‐effect approach incorporating data from four Phase 1 or 1/2 studies, followed by model refinement and inclusion of two Phase 1 and one Phase 3 studies. Results: The final model was developed with 5588 concentrations from 631 subjects with doses of 160–640 mg. Custirsen PK was adequately described by a three‐compartment model with first‐order elimination. For a representative 66‐year‐old individual with body weight 82 kg and serum creatinine level 0.933 mg dl −1, the estimated typical (95% CI) parameter values were clearance ( CL ) = 2.36 (2.30–2.42) l h −1, central volume of distribution ( V 1 ) = 6.08 (5.93–6.23) l, peripheral volume of distribution ( V 2 ) = 1.13 (1.01–1.25) l, volume of the second peripheral compartment ( V 3 ) = 15.8 (14.6–17.0) l, inter‐compartmental clearance Q 2 = 0.0755 (0.0689–0.0821) l h −1, and Q 3 = 0.0573 (0.0532–0.0614) l h −1 . Age, weight and serum creatinine were predictors of CL ; age was a predictor of Q 3 . Conclusion: A population PK model for custirsen was successfully developed in cancer patients and healthy subjects, including covariates contributing to variability in custirsen PK.